2005
DOI: 10.1038/nchembio707
|View full text |Cite
|
Sign up to set email alerts
|

Activity-based probes that target diverse cysteine protease families

Abstract: Proteases are one of the largest and best-characterized families of enzymes in the human proteome. Unfortunately, the understanding of protease function in the context of complex proteolytic cascades remains in its infancy. One major reason for this gap in understanding is the lack of technologies that allow direct assessment of protease activity. We report here an optimized solid-phase synthesis protocol that allows rapid generation of activity-based probes (ABPs) targeting a range of cysteine protease famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
284
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 335 publications
(291 citation statements)
references
References 27 publications
3
284
0
2
Order By: Relevance
“…For these studies, we obtained three commercially available inhibitors (Z-DEVD-FMK, Z-IETD-FMK, and Z-LEHD-FMK) equipped with a fluoromethylketone (FMK) reactive group. We also synthesized three inhibitors that contained the same peptide sequences (NP-DEVD-AOMK, NP-LETD-AOMK, and NP-LEHD-AOMK) but linked to the acyloxymethylketone (AOMK) reactive group shown previously to be effective towards caspases [7,8] ( Figure 1A). To test inhibitor selectivity against caspases 3, 7, and 9 we used an apoptotic proteome in which the intrinsic apoptotic pathway is activated through addition of cytochrome c and dATP [9].…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…For these studies, we obtained three commercially available inhibitors (Z-DEVD-FMK, Z-IETD-FMK, and Z-LEHD-FMK) equipped with a fluoromethylketone (FMK) reactive group. We also synthesized three inhibitors that contained the same peptide sequences (NP-DEVD-AOMK, NP-LETD-AOMK, and NP-LEHD-AOMK) but linked to the acyloxymethylketone (AOMK) reactive group shown previously to be effective towards caspases [7,8] ( Figure 1A). To test inhibitor selectivity against caspases 3, 7, and 9 we used an apoptotic proteome in which the intrinsic apoptotic pathway is activated through addition of cytochrome c and dATP [9].…”
Section: Dear Editormentioning
confidence: 99%
“…After incubation, the poly-caspase probe KMB01 (biotin-hex-EVD-AOMK) [8] was added to label residual caspase active sites for an additional 30 min. After 10-min incubation with cytochrome c and dATP, KMB01 labels the fully cleaved forms of 20 npg Selectivity of caspase inhibitors…”
Section: Dear Editormentioning
confidence: 99%
“…Activity based probes (ABPs) are reagents that can specifically label active proteases, thus allowing their activity, and more importantly their regulation, to be directly monitored [6,7]. Our laboratory recently reported a synthesis strategy based on the general solid phase methods developed by Ellman and co-workers [8] for the production of peptidyl acyloxymethyl ketone ABPs for diverse cysteine protease activities [9].We have previously demonstrated that the biotinylated ABP b-hex-D-AOMK efficiently labels endogenous legumain in 816 B cell lysates [9]. However this reagent lacks cell permeability and its overall selectivity towards legumain had not been extensively examined.…”
mentioning
confidence: 99%
“…Activity based probes (ABPs) are reagents that can specifically label active proteases, thus allowing their activity, and more importantly their regulation, to be directly monitored [6,7]. Our laboratory recently reported a synthesis strategy based on the general solid phase methods developed by Ellman and co-workers [8] for the production of peptidyl acyloxymethyl ketone ABPs for diverse cysteine protease activities [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation